1995
DOI: 10.1002/hep.1840220420
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of cytokines on the inducible expression of CYP1A1, CYP1A2, and CYP3A4 in human hepatocytes in primary culture

Abstract: We have investigated the effect of cytokines, including interleukin-6 (Il-6), interleukin-la (Il-la), and tumor necrosis factor-alpha ("Fa), on the inducible expression of cytochrome P450s (CYP) CYPlA1, CYPlA2, and CYP3A4 in human hepatocytes in primary culture. The ability of these cultures to mimic the acute phase response when stimulated with cytokines was evaluated using immunoblotting to measure the production of albumin, ferritin, fibrinogen, and ceruloplasmin. The cytokines exhibited specific patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 27 publications
4
126
1
1
Order By: Relevance
“…In vitro studies in hepatoma cell lines illustrate the downregulation of Cyp3a11 exposed to the proinflammatory cytokines IL-6, IL-1b and TNF-a (Lee and Piquette-Miller, 2001;Sukhai et al, 2001). Furthermore, the inducible expression of CYP3A4 by rifampicin in human primary hepatocytes in culture is abrogated by the administration of IL-6, suggesting a central role of IL-6 in the repression of CYP3A (Muntane-Relat et al, 1995;Guillen et al, 1998). On administration of these cytokines to rodents, reproducible reductions of Cyp3a mRNA expression with IL-1b, TNF-a and especially IL-6 were observed (Ghezzi et al, 1986a, b;Ferrari et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies in hepatoma cell lines illustrate the downregulation of Cyp3a11 exposed to the proinflammatory cytokines IL-6, IL-1b and TNF-a (Lee and Piquette-Miller, 2001;Sukhai et al, 2001). Furthermore, the inducible expression of CYP3A4 by rifampicin in human primary hepatocytes in culture is abrogated by the administration of IL-6, suggesting a central role of IL-6 in the repression of CYP3A (Muntane-Relat et al, 1995;Guillen et al, 1998). On administration of these cytokines to rodents, reproducible reductions of Cyp3a mRNA expression with IL-1b, TNF-a and especially IL-6 were observed (Ghezzi et al, 1986a, b;Ferrari et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…7 Several comparative studies have shown that, in general, all tested inflammatory mediators caused CYP downregulation with more or less similar efficiency. [8][9][10] However, from these studies it is difficult to estimate the relevance of each cytokine within the inflammatory process. Thus, the aim of the present study was to investigate the role of IL-6 in the down-regulation of specific CYP isoforms during inflammation in vivo using IL-6 Ϫ/Ϫ mice and compare it with the behavior of extracellular and intracellular APPs.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 During pathologic disorders leading to activation of the inflammatory acute-phase response, impairment of CYP metabolic activity and decrease in total hepatic CYP content have been described (reviewed in Morgan 7 ). In vitro studies using hepatocytes [8][9][10][11][12] as well as in vivo studies in humans 13,14 and rodents [15][16][17] have shown that cytokines released during inflammation, like interleukin 1 (IL-1), tumor necrosis factor ␣ (TNF-␣), IL-6, and interferon, can down-regulate hepatic CYP through a still not well-established mechanism leading to transcriptional inhibition of CYP genes. 9,18 Despite the fact that all cytokines examined cause a characteristic CYP repression, their relevance in vivo remains to be elucidated.…”
mentioning
confidence: 99%
“…In fact, TNF and other proinflammatory cytokines have been shown to downregulate CYPs. 38,[58][59][60] Three lines of evidence, however, strongly suggest that the rate and extent of APAP bioactivation were similar in wild-type and TNF/LT-␣-deficient mice. First, the microsomal activity of the major CYP form (CYP2E1) that catalyzes the formation of NAPQI and that of CYP1A2 were unaltered in the knockout mice.…”
Section: Discussionmentioning
confidence: 99%